Tools Facilitating Communication for the Deaf - Luz Magnolia Tilano-Vega; Andrés Mauricio Cárdenas-Torres; Isabel Cristina Betancur-Caro; León Mauricio Rivera-Muñoz; Beatriz Liliana Gómez-Gómez; Arango-Restrepo Juan Pablo; Yadira Moreno-Asprilla; Alexandra Jaramillo-Velásquez (Universidad de La Sabana, 2014)
There is a great deal of interest worldwide in serving people with diverse abilities and needs, especially in the field of education. This implies a commitment to inclusion, empowerment and creating opportunities in a range of sectors. The deaf pose a considerable challenge to any proposal for inclusion and social integration, because their difficulty affects communication. The purpose of this study is to contribute to theoretical reflection on the development of communication tools that give the deaf access to education. It is based on a review of studies found in databases, on institutional websites and in journals on disciplines such as teaching, psychology and engineering. The various tools that have been created to help members of the deaf community strengthen the social, educational, recreational and work-related aspects of their lives are listed.